(untitled) (Proceeding of SINERGY, 2026)
This study focuses on the systematic review and synthesis of empirical findings discussing the role of Accounting Information Systems (AIS) in improving the quality of managerial decision-making. The approach used is a Systematic Literature Review (SLR) by analyzing empirical research articles published in reputable scientific journals, both national and international. The SLR stages were carried out in a structured manner through the process of identifying, filtering, analyzing, and synthesizing literature relevant to the research focus. The results of the review show that the implementation of AIS consistently contributes positively to improving the quality of managerial decisions by providing relevant, accurate, complete, and timely information. The research findings also show that the effectiveness of AIS is not solely determined by the quality of the system and technology, but is also influenced by user competence, top management support, and the level of system suitability to organizational needs. In addition, AIS has been proven to have a strategic role in supporting the planning, control, and performance evaluation processes of organizations in various sectors. This research enriches the accounting literature by strengthening the conceptual understanding of the role of AIS while providing practical implications for management in optimizing the use of accounting information systems to support data-driven decision making.